The Impact of Compensation and Work Environment on Employee Job Satisfaction in the Hospitality Industry (Case Study of Kampung Sumber Alam Hotel and Resort) - Rustandi, Deni; Nankus, Isfan Anbar (Golden Ratio of Data in Summary, 2023)
The hospitality industry has an important role in supporting the growth of the tourism sector in Indonesia. However, one of the main challenges in this industry is maintaining employee job satisfaction so that productivity and service quality remain optimal. This study aims to analyse the effect of compensation and work environment on employee job satisfaction at Kampung Sumber Alam Hotel and Resort. This research uses quantitative methods with descriptive and associative approaches. The population in this study were all employees of Kampung Sumber Alam Hotel and Resort, with simple random sampling technique so that a sample of 55 employees was obtained. Data were collected through questionnaires and analysed using multiple linear regression. The results showed that fair compensation and a conducive work environment had a significant effect on employee job satisfaction. Employees who feel valued with fair compensation and work in a supportive environment tend to be more motivated and have a higher level of job satisfaction. The implication of this study shows that hotel management needs to improve the compensation system based on achievement and length of service and create a more harmonious work environment in order to increase employee loyalty and productivity.